2021
DOI: 10.1088/1367-2630/abd205
|View full text |Cite
|
Sign up to set email alerts
|

Stacking-tailoring quasiparticle energies and interlayer excitons in bilayer Janus MoSSe

Abstract: Stacking sequence of bilayer van der Waals transition metal dichalcogenides determines their electronic and related optical excitations. When the Janus monolayer structure has been taken to construct bilayer TMDs, it would introduce another degree of freedom, the out-of-plane intrinsic dipole moment, to tune the electronic and optical properties. Here we reveal that the electronic band structures and interlayer excitons can be dramatically tuned via the stacking sequence of the bilayer MoSSe with the different… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 58 publications
0
3
0
Order By: Relevance
“…Previous work has shown that the sulfur group elements in each MXY monolayer play different roles in band structures, resulting in a variety of band structures under different stacking orders. 55,56 Therefore, it is of great significance to explore A large band offset is beneficial for electron-hole separation in heterostructures to obtain a longer lifetime of IX, while the intrinsic dipole moment in MoSSe/WSSe would increase the band offset furthermore. 57 The band offset and dipole moments of the three stacking configurations are shown in Table 1, and the dipole moments of the heterostructure composed of the 1T phase MoSSe and WSSe monolayers are also shown in Table S2.…”
Section: Resultsmentioning
confidence: 99%
“…Previous work has shown that the sulfur group elements in each MXY monolayer play different roles in band structures, resulting in a variety of band structures under different stacking orders. 55,56 Therefore, it is of great significance to explore A large band offset is beneficial for electron-hole separation in heterostructures to obtain a longer lifetime of IX, while the intrinsic dipole moment in MoSSe/WSSe would increase the band offset furthermore. 57 The band offset and dipole moments of the three stacking configurations are shown in Table 1, and the dipole moments of the heterostructure composed of the 1T phase MoSSe and WSSe monolayers are also shown in Table S2.…”
Section: Resultsmentioning
confidence: 99%
“…40 the intrinsic electric field, with a possible reordering of IP and IL excitons, was done recently for Janus-bilayers. 41 In this paper, we propose that combining a non-Janus TMD monolayer with a Janus monolayer�thus creating a TMD@ JTMD heterostructure�allows for reliable tuning of the relative order of the IP and IL excitons, in turn leading to an efficient pathway for IP-to-IL conversion via exciton−phonon scattering. Experimentally, Trivedi et al 42 have already shown the controllable room temperature fabrication and optical characterization of TMD@JTMD and JTMD@JTMD HBL crystals.…”
mentioning
confidence: 99%
“…Janus monolayers have been experimentally demonstrated in samples with high structural and optical quality . A first theoretical prediction of the impact of the intrinsic electric field, with a possible reordering of IP and IL excitons, was done recently for Janus-bilayers . In this paper, we propose that combining a non-Janus TMD monolayer with a Janus monolayerthus creating a TMD@JTMD heterostructureallows for reliable tuning of the relative order of the IP and IL excitons, in turn leading to an efficient pathway for IP-to-IL conversion via exciton–phonon scattering.…”
mentioning
confidence: 99%